Avaliação psicofísica cromática e acromática de pessoas em tratamento da Hanseníase - Soares, Perla Figueredo Carreiro (2015)
This study aimed to verify if there are differences in chromatic and achromatic vision between a study group (GE) composed of people with leprosy and a control group (CG) without leprosy diagnosis. Participants were 16 people, seven from GE, with the average age of 30.86 years (SD = 5.52), the average educational level of 9 years (SD = 4.72) and nine of CG, with the average age of 30.89 (SD = 5.88) and the average educational level of 9.78 years (SD = 1.92). For the screening and initial evaluation, the socio-demographic questionnaire (DSD), the Visual Acuity (AV) and the Ishihara Test were used. After this initial stage, the Cambridge Color Test (CCT) and the Lanthony Desaturated D15 were used to evaluate the color perception and the Contrast Sensitivity Function (FSC) to measure achromatic grid perception. All tests were performed binocularly. The results showed significant differences in the Color Confusion Index (CI) (t = 3.49, p <0.01) between the SG (M = 1.65, SD = 0.52) and the GC , 05, SD = 0.04). There was a positive correlation of CHF with leprosy treatment time (r =, 83, p <0.01). In the triangular protocol of the CCT, the GE showed higher the average values in the protan (GC = 39, GE = 48), deutan (GC = 46, GE = 69) and tritan (GC = 59; data showed significant difference only for the protan axis (t = 4.86, p <0.05). There was a positive and significant correlation between the length of the protan axes (ρ = 0.022, p <0.05) and deutan (ρ = 0.036, p <0.05) with age. For the ellipse protocol, the GE presented higher averages in the three areas of ellipse A1, A2 and A3, and there was a significant difference in all areas, A1 (t = 5.74, p <0.05), A2 (t = 7.95, p <0.05) and A3 (t = 5.71, p <0.05). The area of ellipse A3 (tritan) positively correlated with age (ρ = 0.023, p <0.05) and ICC (r =, 68, p = 0.005) and negatively with schooling (r = -50, p = 0.047 ). In areas A1 (r =, 59, p = 0.015) and A2 (r =, 93; p = 0.000) there was a positive correlation with CHF. In the achromatic evaluation, the ANOVA On Way showed a significant difference (F = 9.13, p <0.001), while the Turkey test showed that the average contrast sensitivity (SC) of the EG was lower than that of the GC in all frequencies, except for the 1.0 cpp frequency, with a significant difference only for the high frequencies: 5.0 (p <0.05); 10.0 (p = 0.004 or p <0.05) and 16.0 cpg (p <0.05). There was a significant negative correlation for CHF and the frequencies 5.0 cpg (r = -, 59; p = 0.014); 10.0 cpg (r = -, 66, p = 0.005) and 16.0 cpg (r = -, 68, p = 0.003), understanding that the lower the SC in those frequencies the higher the CHF. There was a negative correlation between the area of the ellipse protocol of CCT A2 and the three frequencies 5.0 cpg (r = -, 61; p <0.012); 10.0 cpg (r = -65, p <0.006) and 16.0 cpg (r = -.53, p <0.034). This study points to evidence of psychophysical consequences, more specifically visual perception for color and sensitivity to contrast of luminance in people with leprosy.